1997
DOI: 10.1097/00001648-199701000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Other Risk Factors for Renal Cell Carcinoma in Postmenopausal Women

Abstract: Among 35,192 postmenopausal, predominantly white women in Iowa age 55-69 years and free of cancer, we collected baseline history, dietary information, and anthropometric data by mail in 1986. We ascertained the 8-year incidence (62 new cases) of renal cell carcinoma using the Iowa Surveillance, Epidemiology, and End Results (SEER) register, the National Death Index, and mail follow-up. Risk factors for renal cell carcinoma included increasing age, increasing weight (either current, maximum adult weight, or wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
83
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 18 publications
13
83
5
Order By: Relevance
“…Aligned with our observations, previous case‐control,6, 34 individual cohort21 and pooled cohort22 studies have demonstrated significant associations between intake of carotenoids and RCC risk 34, 35, 36. However, other case‐control37 and cohort5, 7, 8, 14, 23 studies did not detect an association. Reasons for discrepancies in findings among dietary risk factor studies may be due to differences in the source populations, variations in dietary assessment methods, and varying degrees of recall bias between studies.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Aligned with our observations, previous case‐control,6, 34 individual cohort21 and pooled cohort22 studies have demonstrated significant associations between intake of carotenoids and RCC risk 34, 35, 36. However, other case‐control37 and cohort5, 7, 8, 14, 23 studies did not detect an association. Reasons for discrepancies in findings among dietary risk factor studies may be due to differences in the source populations, variations in dietary assessment methods, and varying degrees of recall bias between studies.…”
Section: Discussionsupporting
confidence: 87%
“…Aligned with these observations, previous studies demonstrated an association between increased intake of tocopherols with decreasing RCC risk for males and females, nonsmokers, and ever smokers 5, 36, 37, 38, 39, 40. In contrast, other studies reported associations of marginal or no significance between RCC risk and tocopherol intake 7, 8, 10, 14, 15, 41…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations